Spontaneous hepatic rupture: A catastrophic complication in a patient with primary splenic angiosarcoma and hepatic metastasis: case report and literature review - Wu, Zhidan; Cao, Xiangming; Zuo, Yuanyuan; Zheng, Yongqiang (Frontiers in Oncology, 2025)
BackgroundPrimary splenic angiosarcoma (PSA) is an exceedingly rare and aggressive malignancy with a poor prognosis. This report aims to present a rare case of PSA that progressed to fatal hepatic rupture due to rapid metastatic spread following splenectomy and adjuvant therapy; a review of the relevant literature is also provided to discuss the diagnostic and therapeutic challenges associated with this condition.Case presentationA 52-year-old male patient presented with acute abdominal pain and hypovolemic shock. Imaging revealed splenic rupture with hemoperitoneum. An emergency splenectomy was performed, and histopathological examination confirmed the diagnosis of angiosarcoma. The patient received postoperative chemotherapy (liposomal paclitaxel) and subsequent targeted therapy (sunitinib). However, rapid hepatic metastasis occurred, leading to spontaneous hepatic rupture and death 6 months after the initial diagnosis.ConclusionThe condition poses a diagnostic and therapeutic challenge due to its nonspecific presentation and high aggressiveness. Early splenectomy remains the prevailing standard of care. This case demonstrates the potential inefficacy of sunitinib against PSA-derived hepatic metastases and emphasizes the critical importance of early diagnosis and intervention before splenic rupture occurs. The potential for combination therapies, including immunotherapy, to represent future investigative avenues is a promising area for future research.